Combined effects of vertical and lateral confinement on the magnetic properties of MnAs micro and nano-ribbons - Steren, Laura Beatriz (2016)
The micromagnetic domain structure of MnAs films gave place to an intense research activity in the last few years due to its potential application in magneto-electronic devices such as domain-wall track memories and logic circuits. These applications require a full knowledge of miniaturization effects on the magnetic properties of the material. In this work, X-ray photoemission electron microscopy has been used for imaging magnetic domains in lithographically fabricated MnAs ribbons, addressing the dependence of the domain configuration on film thickness and ribbon width. Our experiments show a transition from head-on to regular stripe domains below a critical width/thickness ratio wc ≈ 6. Micromagnetic simulations suggest that this transition is correlated to the magnetic structure of the surface plane. Depending on the ribbon width and thickness, the magnetic configuration is shown to evolve from flux-closure domain structure to a state of almost homogeneous magnetization, observed for narrower ribbons. The evolution of the domain structure, magnetic fraction, and magnetization with temperature has been studied across the ferromagnetic/paramagnetic transition. Our experiments show that the magnetic configuration in ribbons exhibits higher stability to temperature variations than in as-cast films.